Informational approach of family spin-offs in the funding process of innovative projects: An empirical verification - Francesco Campanella; Manlio Del Giudice; Maria Rosaria Della Peruta (Journal of Innovation and Entrepreneurship, 2013)
In recent years, the increase in competitiveness, as a result of the economic globalization and crisis, has caused the bankruptcy of many Italian small family businesses working in traditional industries. Meanwhile, family firms that have been working in a perspective of process and product innovation have been able to maintain a durable competitive advantage. In particular, enterprises that have shown a particular vitality are spin-offs, founded by an innovator entrepreneur with an academic background: these have often found their funding in self-financing and family and public resources in the pre-seed and seed stages of the project. However, these spin-offs often have difficulty financing the start-up phase of the project with external resources due to risk and informational opacity related to innovative processes. The literature grounded on innovation funding has highlighted the informative opacity problem mainly caused by family entrepreneurs' difficulty to communicate innovation characteristics and commercial potential to financial markets and by the inability to identify individuals who are more available to finance innovative investments. Therefore, it is particularly difficult for investors to assess family small- and medium-sized enterprises' economic feasibility of innovative projects. These difficulties have increased in recent years partly due to the economic crisis that, on the one hand, has made venture capitalists more risk averse and, on the other, has contributed to a gradual hardening of enterprises' creditworthiness system adopted by financial brokers. The research focuses on the analysis of the information problem that hinders the external financing aimed at innovation in family academic spin-offs. In particular, the authors intend to investigate the information dynamics between the innovator entrepreneur and external financiers. So, this research is useful to better identify what informative gaps impede innovative investments in Italy among innovator entrepreneurs and founders through venture capital and debt capital.
Keywords: 650